Optimizing Energy Baseline for Medium Size Office Using Hybrid EnergyPlus-Evolutionary Programming (EP) - Dahlan, N. Y.; M. Aris, A. A. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
This paper presents an optimization approach of developing building energy baseline for medium sized office using Evolutionary Programming (EP) in comparison with direct methods. This paper applies simulation-based approach by coupling Matlab and EnergyPlus to perform energy building simulation and obtain the best energy baseline configuration with minimal error. On the other hand, direct method relies on try-and-error manually key-in methods using OpenStudio EnergyPlus simulation software. The proposed method is applied to a single story Green Energy Research Centre (GERC) office building located in UiTM Shah Alam with characteristic of partially air-conditioned buildings. The office consists of 5 different size rooms with different purposes. In this regard, 3 building parameters are taken as a decision variables including occupancies, lightings and electrical equipment. The EP objective function was set to minimize the difference between simulated and monitored energy consumption. To evaluate accuracy of building energy model, hourly criteria for Normalized Mean Biased Error (NMBE) and Coefficient of Variance Root Mean Squared Error (CV(RMSE)) endorsed by IPMVP were used. It is found that simulation-based approach has lower value of NMBE at 2.775% and CV(RMSE) at 10.949% compared to direct methods where NMBE at 79.964% while CV(RMSE) at 104.848%.